The Lion-Demon in the Art of Mesopotamia and Neighbouring Regions. Materials Towards the Encyclopaedia of Mesopotamian Religious Iconography, 1/1 - Green, Anthony
grew out of a chapter in his doctoral thesis Neo-Assyrian Apotropaic Figures, with Special Reference to the Human "Heroes" and Human-Animal Hybrids: Iconography, Chronology, Identification and Significance. Faculty of Arts, University of Manchester, 1983; see BaM 17,239 and Index to Theses Accepted for Higher Degrees by the Universities of Great Britain and Ireland, vol.35, part I (London 1986, Aslib), no. 35-0339